Faktor Risiko Kejadian Ispa Pada Balita DiWilayah Kerja Puskesmas Sukoharjo - Murti, Tri, Badar Kirwono, SKM., M.Kes, Kusuma Estu Werdani, SKM., M.Kes (2016)
Acute Respiratory Infections (ARI) became the first cause of infant mortality in developing countries. The prevalence of ARI in infants in Sukoharjo district in 2011 as many as 142 cases (2.2%), in 2012 as many as 87 cases (1.3%), in 2013 as many as 171 cases (12.4%) with patients in PuskesmasSukoharjo as many as 40 children (30.0%).This study aims to determine the dominant risk factors ARI in infants in Puskesmas Sukoharjo.This type of research is observational research with case control approach. The populations in this study are all mothers or parents who have children suffering from ARI and not ARI. Selection of samples using Exhaustive Sampling by the number of research subjects in the case as many as 40 samples and 40 control samples. Bivariate analysis is using Chisquare and multivariate analysis using logistic regression. The results of the bivariate studies using a link between parental knowledge (p = 0.001), there is a relationship between ventilation (p = 0.001), there is a relationship between cigarette smoking family members (p = 0.006) with ARI in infants in Puskesmas Sukoharjo. While the multivariate results show that the knowledge of parents had the highest OR amounted to 8.752 (95% CI = 2.764 to 27.712), its mean that parents who have poor knowledge about ARI risk amounted to 8.752 times to experience ARI in infants.